2022
DOI: 10.1002/adfm.202200322
|View full text |Cite
|
Sign up to set email alerts
|

Countering Voltage Decay, Redox Sluggishness, and Calendering Incompatibility by Near‐Zero‐Strain Interphase in Lithium‐Rich, Manganese‐Based Layered Oxide Electrodes

Abstract: Lithium‐rich, manganese‐based layered oxides are considered one of the most valuable cathode materials for the next generation of high‐energy density lithium‐ion batteries (LIBs) for their high specific capacity and low cost. However, their practical implementation in LIBs is hindered by the rapid voltage/capacity decay on cycling and the long‐standing contradictions between redox kinetics and volumetric energy density due to their poor calendaring compatibility. Herein, a coherent near‐zero‐strain interphase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…This study demonstrated that adding a protective layer can significantly hinder volume expansion. Similarly, He et al 76 used the reactive infiltration method (RIM) to inject Li-ion conductive near-zero-strain LiAlO 2 (LAO) into the grain boundary of Li 1.2 [Mn 0.54 Ni 0.26 ]O 2 (LRMN) to coat the primary particles (Figure 3). The LAO coating layer can provide mechanical stability to the LRMN owing to its near-zero-strain behavior.…”
Section: Strategies For Achieving Zero-strain Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that adding a protective layer can significantly hinder volume expansion. Similarly, He et al 76 used the reactive infiltration method (RIM) to inject Li-ion conductive near-zero-strain LiAlO 2 (LAO) into the grain boundary of Li 1.2 [Mn 0.54 Ni 0.26 ]O 2 (LRMN) to coat the primary particles (Figure 3). The LAO coating layer can provide mechanical stability to the LRMN owing to its near-zero-strain behavior.…”
Section: Strategies For Achieving Zero-strain Cathodesmentioning
confidence: 99%
“…(b) HAADF-STEM, (c, d) equivalent FFT patterns, and (e–h) energy-dispersive spectroscopy (EDS) mapping of the cross-sectional LAO-LRMN cathode at the grain boundary. Reproduced with permission from ref . Copyright 2022, Wiley-VCH GmbH.…”
Section: Strategies For Achieving Zero-strain Cathodesmentioning
confidence: 99%
“…So far, numerous measures have been taken for modifying the bulk and surface structures and properties of LLOs, such as surface coatings , and elemental doping . Zhao et al obtained a uniform Al 2 O 3 coating on the surface of layered cathode materials using an atomic layer deposition technique and thus achieved the outstanding cycle performance.…”
Section: Introductionmentioning
confidence: 99%
“…Cathode materials are the main bottleneck limiting the energy density of lithium-ion batteries (LIBs), because their specific capacity is usually lower than that of the current anode materials. Therefore, there is an urgent need to explore cathode materials with high voltage and high specific capacity to meet the growing demands for high-energy-density LIBs. , …”
Section: Introductionmentioning
confidence: 99%